The antibacterial effect of methanolic fraction of Nepeta depauperataon against Pseudomonas aeruginosa isolates from burn wound infections - Hakemi vala, Mojdeh; Saifiabolhassan, Zahra -; Bagheri Bejestani, Fatemeh (Novelty in Biomedicine, 2018)
Background: In this study, the antibacterial effect of the methanolic fraction of Nepeta depauperata against 50 isolates of Pseudomonas aeruginosa from burn wound infections of patients who referred to Shahid Motahari hospital of Tehran in 2014 was evaluated. Materials and Methods: All bacterial isolates were confirmed by standard bacteriologic methods. Their resistant to common antibiotics were evaluated by disk diffusion method based on CLSI 2014. The Nepeta depauperata aerial parts were collected from Hormozgan Province and identified. Methanolic extract was prepared by maceration method using percolator apparatus and concentrated by rotary evaporator. The antibacterial activity of methanolic extract were determined by two methods; cup plate diffusion agar for determination the zone diameter of inhibition and microdilution broth for minimum inhibitory concentration (MIC) and further minimum bacteriocidal concentration (MBC). Statistical analysis was done by SPSS software version 20. Results: The percentage of resistance and susceptibility against nine different kinds of common antibiotic disk showed 83% resistance on average as evaluated by agar disk diffusion (Kirby–Bauer antibiotic test). Also, the mean of inhibition zone diameters has been measured in concentrations of 1000, 500, 250 mg/ml as follow: 12.58, 11.3 and 9.44 mm, respectively by cup plate and the amount of 87.93 and 104.78 mg/ml for MIC and MBC were determined, respectively, using the broth microdilution method. Statistic analysis was done with SPSS verssion19 software. Conclusion: According to the satisfying results of the antibacterial effect of the testing methanolic extract against clinical isolates of P. aeruginosa isolates further in vitro and in vivo studies are recommended.